If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying XY = X + Y + 10 Reorder the terms: XY = 10 + X + Y Solving XY = 10 + X + Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. -1X + XY = 10 + X + -1X + Y Combine like terms: X + -1X = 0 -1X + XY = 10 + 0 + Y -1X + XY = 10 + Y Reorder the terms: -10 + -1X + XY + -1Y = 10 + Y + -10 + -1Y Reorder the terms: -10 + -1X + XY + -1Y = 10 + -10 + Y + -1Y Combine like terms: 10 + -10 = 0 -10 + -1X + XY + -1Y = 0 + Y + -1Y -10 + -1X + XY + -1Y = Y + -1Y Combine like terms: Y + -1Y = 0 -10 + -1X + XY + -1Y = 0 The solution to this equation could not be determined.
| 2sin(x+pi)=0 | | 100c+1c=5c | | 3y/4-y/2-5=7 | | 3y/8-6=y/4-5 | | X/2-x/3+x/4=5 | | 6x^2-15x-1=0 | | 8-4x=26-13x | | x^2+7x-35=0 | | 8+8C=6C+88 | | 141-5x=3x+22 | | (1/4)(6x+1)=4x | | 3(y-1)+20=5+3(y+5) | | x-6+2= | | (1/3)-(1/6)+(1/4) | | 6x+3x-9=9 | | 5/7x+4=-1 | | 3.33(12-0.2x)x^(3/2) | | x/-5=-15 | | 3.33(12-0.2x)x^3/2 | | 8-p=-12-39 | | 4d+5=3 | | 3x+3x=5x+7 | | 260-3x=42x+15 | | -7a^2= | | 49+20(2)= | | -2a+2=1 | | 6-8x=15-36x | | 6-8x=15-6x | | x^2-11x+25=3x+1 | | 6=5x-5 | | 3-y=-31 | | 7-2x=x |